(untitled) (Eurasian Journal of Engineering and Technology, 2022)
This article states that it would be expedient to establish health-improving sanatoriums for human health on the shores of Dengizkul and Shurkul, and in the future to establish seasonal and non-seasonal ecotourism zones for the rational use and preservation of natural resources.